A phase II study of monalizumab in patients with recurrent/metastatic squamous cell carcinoma of the head and neck: The I1 cohort of the EORTC-HNCG-1559 UPSTREAM trial. (November 2021) - Galot, Rachel; Le Tourneau, Christophe; Saada-Bouzid, Esma; Daste, Amaury; Even, Caroline; Debruyne, Philip; Henry, Stéphanie; Zanetta, Sylvie; Rutten, Anemie; Licitra, Lisa; Canon, Jean-Luc; Kaminsky, Marie-Christine; et al.
Abstract: Purpose: Monalizumab is a monoclonal antibody targeting the inhibitory natural killer group 2A (NKG2A) receptor localised on natural killer (NK) and T cells. Its ligand, the human leukocyte antigen E (HLA-E), is overexpressed in squamous cell carcinoma of the head and neck (SCCHN). By targeting the HLA-E-NKG2A pathway, monalizumab may enhance NK and T cell activity. Experimental design: The UPSTREAM trial is a biomarker-driven umbrella trial studying targeted therapies and immunotherapies in patients with recurrent/metastatic (R/M) SCCHN progressing after platinum therapy. The immunotherapy 1 (I1) cohort was a phase II, single-arm substudy evaluating monalizumab (10 mg/kg intravenously on day 1 of a 14-day cycle). The primary end-point was the objective response (OR) rate (Response Evaluation Criteria in Solid Tumours 1.1) over the first 16 weeks. A two-stage Simon design was used (H1 15%, H0 3%, α 8%, power 90%) with pre-planned interruption of accrual if no OR was observed after the first 25 patients. Results: Twenty-six eligible patients were enrolled. Seventeen (65%) patients had received ≥2 previous lines of systemic treatment, and 15 (58%) patients were PD(-L)1 inhibitor pretreated. No OR was observed. Stable disease was observed in 6 patients (23%) with a median duration of 3.8 months (95% confidence interval [CI]: 2.7–NE). The median progression-free survival and overall survival were 1.7 months (95% CI: 1.5–1.8) and 6.7 months (95% CI: 3.0–9.6), respectively. The most frequent treatment-related adverse event was grade I/II fatigue (19%). Conclusions: Monalizumab monotherapy has limited activity in R/M SCCHN. The I1 cohort did not meet its primary objective. Monalizumab combined with durvalumab is under investigation within UPSTREAM. Highlights: This study demonstrates the feasibility of UPSTREAM, a biomarker-driven trial for SCCHN. This is the first trial of monalizumab monotherapy in SCCHN. Disease stabilization was observed in 23% of the patients. Patients previously exposed to PD-(L)1 inhibitors had a higher median OS.